Digital Divide and Classifying Social Class in Rural Development: Voices from the Secondary Data of Field - Tresna Putra Anugrah, Gilang; Sjaf, Sofyan; Hermansah, Tantan (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2024)
This paper aims to investigate the digital divide and to classify social class as a significant indicator in the context of rural development. The study employed secondary data analysis derived from the Data Desa Presisi (DDP). The researcher meticulously analyzed and reinterpreted statistical data to identify new potential avenues for development planning, with a particular focus on Neglasari Village. The findings indicate that the predominant social class in the research area consists largely of lower-class individuals or casual laborers, who are categorized as impoverished in terms of rural development. This categorization aligns with the conclusion that poverty, as revealed through social class mapping, contributes to the digital divide, which is predominantly influenced by the upper social class. Consequently, this dynamic tends to create a segmentation of development information at the initial level. Conversely, it is noteworthy that the lower class exhibits the highest purchasing power for communication expenses, raising questions about the effectiveness and utility of network access and communication costs. This study serves as a valuable resource for village development planners, emphasizing the importance of considering the dynamics of social class, the implications of the digital divide, and the necessity for evaluative and accountable development monitoring models in the distribution of targeted programs.